2022
DOI: 10.3390/insects14010020
|View full text |Cite
|
Sign up to set email alerts
|

Leaf UV-B Irradiation and Mycorrhizal Symbionts Affect Lettuce VOC Emissions and Defence Mechanisms, but Not Aphid Feeding Preferences

Abstract: Arbuscular mycorrhizal fungi (AMF) and ultraviolet-B radiation (UV-B) play important roles in plant–insect interactions by altering plant physiology and histology. We hypothesized that UV-B-induced oxidative stress was mitigated by AMF symbiosis. In this study, we conducted a multifactorial experiment to explore lettuce plant response to AMF inoculation and UV-B exposure (0.4 W m−2; 16 h d−1; 2 weeks), either together or individually, as well as the interaction with the polyphagous insect pest Myzus persicae (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…Other studies reported the marginal effect of UV-B treatment on different Spodoptera species (Lindroth et al 2000 ; Wargent and Jordan 2013 ). Our findings support the hypothesis that generalist herbivores, such as lepidopteran caterpillars or polyphagous aphids [e.g., Myzus persicae (Sulzer)] (Zeni et al 2023 ), have evolved the ability to withstand the chemical defense mechanisms of a wide range of plant species. However, it is important to consider that higher UV-B doses than the one used in this work could further enhance the biochemical defenses in terms of phenolic accumulation, without impairing plant growth and development.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Other studies reported the marginal effect of UV-B treatment on different Spodoptera species (Lindroth et al 2000 ; Wargent and Jordan 2013 ). Our findings support the hypothesis that generalist herbivores, such as lepidopteran caterpillars or polyphagous aphids [e.g., Myzus persicae (Sulzer)] (Zeni et al 2023 ), have evolved the ability to withstand the chemical defense mechanisms of a wide range of plant species. However, it is important to consider that higher UV-B doses than the one used in this work could further enhance the biochemical defenses in terms of phenolic accumulation, without impairing plant growth and development.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, UV-B irradiation priming over AMF inoculation of the most suitable plant genotype may represent a promising approach to increase the nutraceutical and commercial quality of lettuce plants. The enhanced chemical defenses of plants did not impact the feeding behavior of S. littoralis larvae, probably due to (i) the generalist feeding traits of such herbivores, (ii) the mild UV-B treatments, and (iii) the limited time for the induction of mycorrhizal effects on plant secondary metabolism (see also Zeni et al 2023 ). Therefore, further investigations are needed to assess whether different doses of UV-B/AMF and exposure durations (smaller or greater) that increase plant antioxidant defenses within a hormetic framework may alter the feeding behavior of oligophagous insect pests.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations